Can Politicians Say That? What Shapes Public Responses to Speech Scandals - Gift, Thomas; Lastra Anadón, Carlos (Cambridge University Press, 2025)
Why do some politicians face greater backlash for using insensitive language against identity groups while others do not? Existing explanations focus either on the content of speech or the context in which it occurs. In this article, we propose an integrated framework that considers both and test it using a preregistered conjoint survey on a national U.S. sample. Our findings provide partial support for our expectations. Subjects react most negatively to insensitive speech when the target belongs to their own identity group, when aggravating circumstances exist, and when politicians are of an opposing political party. Our article extends growing scholarship on speech scandals, which has largely explained the fates of politicians as a function of a small number of causative variables in isolation.
Keywords: 59 Ciencia Política::5906 Sociología política; ODS 10 - Reducción de las desigualdades; ODS 16 - Paz, justicia e instituciones sólidas; speech; language; identity; political behavior; experiment